Analysis of the Taylor Curve Trade-Off in the United States - Kavřík, Dominik (2021)
The optimal monetary policy faces a trade-off between variabilities of inflation and the output gap. This trade-off, proposed by John B. Taylor in 1979, is represented graphically by the so-called Taylor curve. The negatively sloped curve serves as an efficiency frontier, which implies that if the monetary policy carried out by the central bank is optimal, the observed relationship between the volatilities of the output gap and inflation should be negative. Further to the previous literature, I use the latest data for the United States to investigate the Taylor curve trade-off. Conditional volatilities are obtained using the multivariate GARCH model. The empirical results are consistent with the literature studying the monetary policy before the financial crisis. Regarding the recent period, the monetary policy seems to be sub-optimal after the culmination of the financial crisis in late 2008. The empirical results imply that the variability trade-off does not hold in the period from 2009:Q1 to 2018:Q3.